Ductility of continuous RC beams strengthened with partially bonded near-surface mounted CFRP bars - Mahmoud A. Abdelraouf; Ayman H. Khalil; Ahmed F. Maree; Amr M. Ibrahim (Journal of King Saud University: Engineering Sciences)
Abstract Carbon fiber–reinforced polymer (CFRP) rods have been implemented for repair and strengthening work in several applications for reinforced concrete (RC) elements. The linear brittle behavior of these composite materials can be an excessive limitation for assuring the required level of ductility and moment redistribution. This research work aims to evaluate the ductility and moment redistribution for statically indeterminate RC beams strengthened with partially bonded near-surface mounted CFRP rods. Finite element models were developed and validated based on experimentally tested beams available in the literature. Four model specimens were created for verification, one control continuous beam without strengthening and the others initially strengthened with CFRP bars in both sagging and hogging regions simultaneously with variable bar lengths and CFRP reinforcement ratios. The developed models showed good correlation compared to the experimental results. Then, a comprehensive parametric study was performed to expand the results using different CFRP bonded lengths, CFRP reinforcement ratios, retrofit patterns, and steel reinforcement ratios. The obtained results indicate that partially bonding the CFRP bars can improve the beam’s deformability, ductility, and moment redistribution. The moment redistribution can be further enhanced making use of the combined positive effect of decreasing bonded length and steel/CFRP reinforcement ratios between hogging and sagging regions.